Multipoint sensing for energy efficient operation in buildings - Zhang, Han Wen (2015)
This report is a study of Multipoint sensing information in the various scenario and the energy efficiency of the air-conditioning. A software called FloVENT is used for simulation of room models in different scenario. It calculates the temperature, airflow speed, pressure and other parameters in the mathematical way, providing the solutions for the models. The first experiment is to find the effect of the multipoint sensing system due to the moving heat source. A testing heat source, represented by 11 visitors, is located in 5 different positions for the sensitivity test of the monitors. The following one intends to find temperature change at various monitor points when the dynamic situation occurs (e.g. visitors coming and leaving the room). In this case, a testing heat source is located near the doorway and represent 7 visitors coming and leaving the room. The next test carried out is for studying the changes in temperature if the ambient temperature goes down. To find the relationship between the air-conditioning flow rate and room temperature, the fourth experiment is continued. At the last, the relationship between the air flow rate and power consumption is studied base on the manufacturer’s data. All the experiments and results are described in detailed in this report.